CFD Simulation of an Industrial PEM Fuel Cell with Local Degradation Effects. Issue 4 (4th August 2020) - Fink, C.; Gößling, S.; Karpenko‐Jereb, L.; Urthaler, P.
Abstract: The polymer electrolyte membrane (PEM) fuel cell model of a commercial software package is presented. The basic performance model is extended by two chemical degradation effects: ionomer degradation and carbon corrosion including platinum oxidation. The ionomer degradation model describes the ionomer mass loss due to hydrogen peroxide formation and subsequent attack of the ionomer by radicals. The carbon corrosion model calculates the carbon mass loss caused by carbon oxidation and the active area reduction due to platinum oxidation. The degradation models are coupled with an agglomerate model of the catalyst layer. The model is validated against measurements on an industrial cell. For these measurements, the cell is equipped with a segmented measuring board, which is used to measure the current density distribution and high frequency resistance of every segment. In order to test the predictability of the model under different operating conditions, measurements for stoichiometry and pressure variations are carried out. Calculated and measured current density distributions of the cell, aged by an accelerated stress test, are compared for the validation of the degradation model. Moreover, 3D simulation results of the fresh and aged cells are analyzed in detail and the influence of operating conditions on fuel cell aging is pointed out.